PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACION DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE TILAPIAS EN EL CANTON CHAGUARPAMBA Y SU COMERCIALIZACION EN LA CIUDAD DE LOJA - Juela Patiño, Marco Junior (2015)
Aquaculture in Ecuador is a relatively recent development in the past decade, this activity has received a major boost from the farm in salt marshes and uplands. Therefore fishery exploitation and development has a potential to become a productive activity giving foods rich in proteins at low cost and generate revenue. Some agencies of public and private projects have been initiated aimed at strengthening farming activity in several regions of the country, in the Sierra trout, tilapia and carp was introduced in order to repopulate the lakes, lagoons and rivers; today it has farms in some provinces, it ie different seasons fish fry whose functions are to provide for extension programs introduced species. Therefore the overall objective of this study was to determine the "FEASIBILITY FOR THE IMPLEMENTATION OF A producer and marketer of tilapia CHAGUARPAMBA CANTON AND MARKETING IN THE CITY OF LOJA" and then analyze the possibility to invest or not in a business like this, because there's natural resources and means necessary for the development of this industry in our province, which help to boost the local economy and the southern region. To carry out this research was necessary to rely on two methods such as deductive and inductive which served to analyze and discern general and specific aspects that are involved in the study; so it was necessary to use such techniques as the survey which was applied to the families of the canton and city of Loja Chaguarpamba by making an accurate sample in order to collect information primary exclusively for research; it also interview which was led by a hyphen key supply or competition in the given location questions. Following this with the market study in the city of Loja was possible to determine potential demand of 88.92%; a real demand of 26.06%; and finally the effective 6 demand of 88.04%. To thereby establish a marketing plan, where the price, place, promotion and advertising of the company was determined. With the development of the technical study the functioning and operation of the project as specified: size, location and engineering of the project, providing a suitable work environment to operate optimally and thus provide a quality product; the company's first year working with 88% of its installed capacity. In the administrative law firm is the organizational structure of the company, and manual functions, being a guide for each of the employees aware of their responsibilities and properly perform their assigned activities. The project will make use of both internal and external sources of funding under the following aspects. Internal sources: 41% of the investment corresponding to $ 35,230.80 will be financed with contributions from partners or working capital. External sources: In order to develop this project is necessary to resort to external sources of financing, so it was decided to work with the National Development Bank with its special line of credit, loan it made in the amount of $ 50,000, for a term of five years with an annual interest rate of 15% which will fund this project and corresponds to 59% of the total investment is 85230.80. Finally in the financial evaluation of various financial indicators allowed to establish the feasibility of the project and are analyzed: Net Present Value (NPV) $ 28,370.35; Internal Rate of Return (IRR) 24.50%; and Cost Benefit Ratio (CBR) for every dollar invested obtain 1.91 gain; Sensitivity analysis with increased costs of 53.95%, with a sensitivity of 0.98 and a decrease in revenues 28.23 with a sensitivity 0.99, the same as demonstrating the feasibility of the project for the creation of the company, in the canton Chaguarpamba and marketing in the city of Loja. This proposal is considered feasible if implemented, to be important for investors looking to invest their money thereby contributing to social, economic and tourist development of the canton.